Manajemen Sekolah Adiwiyata dalam Membangun Karakter Mandiri SD Negeri 2 Kundisari Kabupaten Temanggung - Suryandari, Beti; Kusumaningsih, Widya; Ginting, Rosalina Br. (PGRI Kota Semarang, 2024)
Proper management in the adiwiyata school program will affect the success of the program implemented. This study aims to describe and analyze the activity planning, organizing, implementing, and supervising the adiwiyata school program in building the independent character of SD Negeri 2 Kundisari, Temanggung Regency. The research method uses qualitative methods. Data collection techniques use observation, interview, and documetation techniques. Qualitative data analysis includes data collection, data condensation, data display, conclusion drawing / verification. Test the validity of research results using triangulation techniques. The data obtained from the observations were adjusted to interview data or compared data from research subjects consisting of principals, teachers, students, committees, parents, and adiwiyata teams. The results showed that SD Negeri 2 Kundisari has implemented the adiwiyata school management function appropriately so that the program runs efficiently, effectively and the goals are achieved. This is evidenced by the following activities: (1) program planning is carried out by forming an adiwiyata team, compiling environmental studies, compiling and implementing environmental action plans, as well as supervision and evaluation, (2) organizing is carried out by dividing team tasks and communication and coordination systems (3) implementing activities including environmentally sound policies, implementation of environment-based curriculum, participatory based environmental activities, and management of supporting facilities that Environmentally friendly. (4) supervision includes internal supervision by school principals and teachers, external supervision by the Environment Agency (DLH) and school committees.